Are deep squats a safe and viable exercise? - Schoenfeld, B.; Williams, M. (Strength and Conditioning Journal, 2012)
There is a great deal of debate among strength and conditioning professionals, rehabilitation specialists, and researchers regarding the safety and efficacy of performing the deep squat exercise. In this article, the potential benefits and the potential risks of performing this closed-kinetic chain lower extremity exercise will be discussed.